2014
DOI: 10.1016/j.sbspro.2014.10.268
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing Intercultural Competence: A Phenomenological Investigation of Students’ Intercultural Experiences

Abstract: This paper investigates the notion of intercultural competence from the perspective of students in a Malaysian university. Indepth interviews involving fifteen culturally diverse students were conducted. Students reflected their lived experiences with cultural others and shared their perceptions of competent communication. Using phenomenological analysis of the interview data, two core themes that encompass intercultural competence emerged: acquiring cultural understanding and respecting cultural differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…Yet, the current understanding of intercultural competence was vastly drawn from the Western scholars' perspectives (Yep, 2014). New developments of intercultural communication have indicated calls for more perspectives on intercultural competence of people from other cultures, particularly within the Asian region (see, for example, Asante, Miike & Yin, 2014;Chen, 1993;Dalib, Harun & Yusof, 2014;Xiao & Chen, 2009;Yum, 2012;Halim, Bakar & Mohamad, 2018). Looking into Malaysia's cultural mosaic, Tamam (2015) has claimed that the research of intercultural competence is still underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the current understanding of intercultural competence was vastly drawn from the Western scholars' perspectives (Yep, 2014). New developments of intercultural communication have indicated calls for more perspectives on intercultural competence of people from other cultures, particularly within the Asian region (see, for example, Asante, Miike & Yin, 2014;Chen, 1993;Dalib, Harun & Yusof, 2014;Xiao & Chen, 2009;Yum, 2012;Halim, Bakar & Mohamad, 2018). Looking into Malaysia's cultural mosaic, Tamam (2015) has claimed that the research of intercultural competence is still underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, interaction is a key element in the IC development process (FISCHER, GONDIM, PEREIRA et al, 2009 PORZELT, 2012;SUCHANKOVA, 2014;SOBOLEVA and OBDALOVA, 2014;NAZARENKO, 2014;DUSI, MESSETTI and STEINBACH, 2014;DALIB, HARUN and YUSOFF, 2014). IC is necessary to manage interaction among people in a multicultural context (DUSI, MESSETTI and STEINBACH, 2014), there is a need to develop interpersonal relationship capacities (FISCHER, GONDIM, PEREIRA et al, 2009;BEHRND and PORZELT, 2012), through the understanding of the other (RODRIGUES and PINHEIRO, 2010), the will to interact with people from different cultures (YASHIMA, 2010) and the reciprocity of the contact (LOUGH, 2011).…”
Section: Interactionmentioning
confidence: 99%
“…A recent phenomenological study in Malaysia indicated that intercultural competence is viewed as a co-created process between culturally different members that occurs through interpersonal relationship [1,8]. Drawing from such study, a new conceptual model of intercultural competence has been delineated [1].…”
Section: Probing Intercultural Competence In Malaysiamentioning
confidence: 99%
“…Accordingly, such Euro-American centric definition has led to delineation of theories and perspectives that were Eurocentric in origin [6,13]. Recent development in the studies of intercultural competence indicated a challenge to the application of Eurocentric theories in other cultural settings [1,3,8,9,10]. Thus, calls have been made to re-examine whether the Eurocentric perspectives can be translated into other cultural contexts.…”
Section: Introductionmentioning
confidence: 99%